USM TO INTENSIFY COLLABORATION WITH UNIVERSITÉ DE LORRAINE - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 17 January 2016 – The Universiti Sains Malaysia (USM) Deputy ViceChancellor (Research and Innovation), Professor Dato’ Dr. Muhamad Jantan is urging academicians from USM to intensify collaborations and partnerships with Université de Lorraine (UL) in France, covering various disciplines including research.